2010
DOI: 10.1097/gim.0b013e3181e5c7ea
|View full text |Cite
|
Sign up to set email alerts
|

Spinal extradural arachnoid cysts in lymphedema-distichiasis syndrome

Abstract: Purpose: Lymphedema-distichiasis syndrome is characterized by the presence of lower limb lymphedema and supernumerary eyelashes arising from the Meibomian glands. Spinal extradural arachnoid cysts have been observed in some families but their true frequency is unknown. The aim of this study is to determine the frequency of spinal extradural arachnoid cysts in lymphedema distichiasis syndrome. Methods: We collected clinical information from all 45 living members of a complete family of 48 members and performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 13 publications
1
15
1
Order By: Relevance
“…[ 10 ] The dural defect of SEDAC is considered to be due to abnormal dura mater development. FOXC2 , the disease gene for syndromic SEDAC[ 5 , 6 ] also encodes a homeobox transcription factor and expressed in the developing mesodermal mesenchyme which forms the dura mater. [ 13 15 ] Dura mater development would be impaired by FOXC2 loss of function mutations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 10 ] The dural defect of SEDAC is considered to be due to abnormal dura mater development. FOXC2 , the disease gene for syndromic SEDAC[ 5 , 6 ] also encodes a homeobox transcription factor and expressed in the developing mesodermal mesenchyme which forms the dura mater. [ 13 15 ] Dura mater development would be impaired by FOXC2 loss of function mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic etiology of SEDAC has been suggested. [ 5 , 6 ] We previously investigated 2 familial SEDAC pedigrees associated with lymphedema-distichiasis syndrome (LDS) (OMIM 153400) and identified heterozygous loss of function mutations in FOXC2 (forkhead box C2). [ 6 ] In the study, we also investigated seven sporadic SEDAC patients, but found no FOXC2 mutation.…”
Section: Introductionmentioning
confidence: 99%
“…Most cases of SEDAC are sporadic; however, a few cases of familial SEDAC have been described. 4–7 Their studies showed that familial SEDAC was a part of phenotypes of lymphedema-distichiasis syndrome (LDS; OMIM 153400). LDS is an autosomal dominant disorder with variable expressivity.…”
mentioning
confidence: 99%
“…Its minor phenotypes include ptosis, cleft palate, renal abnormalities, congenital heart disease, vertebral anomalies and SEDAC. 6 , 8–11 LDS was caused by FOXC2 (forkhead box C2) mutations. 6 , 12–16 We previously investigated two pedigrees with familial SEDAC and revealed that both families are related to LDS with variable expression of each phenotype.…”
mentioning
confidence: 99%
See 1 more Smart Citation